2021
DOI: 10.1177/01945998211029839
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Race and Insurance Status on Primary Treatment for HPV‐Associated Oropharyngeal Squamous Cell Carcinoma

Abstract: Objective To assess the impact of sociodemographic factors on primary treatment choice (surgery vs radiotherapy) in patients with human papillomavirus–associated (HPV+) oropharyngeal squamous cell carcinoma (OPSCC). Study Design Retrospective analysis of the National Cancer Database. Setting Data from >1500 Commission on Cancer institutions (academic and community) via the National Cancer Database. Methods Our sample consists of patients diagnosed with HPV+ OPSCC from 2010 to 2015. The primary outcome of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…First, this is a retrospective analysis of the prospectively collected SEER cancer registries, which may be subject to miscoding. The lower rates of surgery in the NHB population may be related to many reasons unavailable within SEER; for example, this association is likely influenced by insurance status 39,40 and comorbidities. 45 Second, we combined Asian, Native American, Native Hawaiian, and Pacific Islander populations to help with data analysis given the small numbers of these populations in the SEER database, but we agree with the current literature 11,59 that caution must be taken aggregating these groups because, within this group, differences exist even in HNSCC outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…First, this is a retrospective analysis of the prospectively collected SEER cancer registries, which may be subject to miscoding. The lower rates of surgery in the NHB population may be related to many reasons unavailable within SEER; for example, this association is likely influenced by insurance status 39,40 and comorbidities. 45 Second, we combined Asian, Native American, Native Hawaiian, and Pacific Islander populations to help with data analysis given the small numbers of these populations in the SEER database, but we agree with the current literature 11,59 that caution must be taken aggregating these groups because, within this group, differences exist even in HNSCC outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Except for Hispanic patients, historically marginalised racial/ethnic groups had disproportionately lower rates of vaccination and decreased knowledge of HPV (online supplemental table 2). Additionally, these populations had lower physician recommendation for vaccination,20–22 higher prevalence of HPV infections23–32 and were less likely to undergo primary surgery as treatment for HPV-associated cancer 33–35. Although vaccination rates among Hispanic patients were relatively high, all historically marginalised racial/ethnic populations had higher rates of HPV-associated cancer36 and worse cancer-related outcomes compared with white patients 37…”
Section: Resultsmentioning
confidence: 99%
“…Regarding HPV-associated cancer, patients with lower income had increased rates of metastasis90 and poorer overall survival outcomes 35 46 48 49. One study found income was not associated with cancer treatment 34…”
Section: Resultsmentioning
confidence: 99%
“…In HPV‐associated oropharyngeal squamous cell carcinoma (OPSCC), Black and nonprivately insured patients are less likely to receive primary surgery when compared with White or privately insured patients 1 …”
mentioning
confidence: 99%
“… Point 1 In HPV‐associated oropharyngeal squamous cell carcinoma (OPSCC), Black and nonprivately insured patients are less likely to receive primary surgery when compared with White or privately insured patients 1 Points 2 and 3 Deaf or hard‐of‐hearing children with unmet hearing care needs are more likely to be from non‐White backgrounds 2 …”
mentioning
confidence: 99%